1995
DOI: 10.1088/0034-4885/58/5/001
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic strings

Abstract: The topic of cosmic strings provides a bridge between the physics of the very small and the very large. They are predicted by some unified theories of particle interactions. If they exist, they may help to explain some of the largest-scale structures seen in the Universe today. They are 'topological defects' that may have been formed at phase transitions in the very early history of the Universe, analogous to those found in some condensed-matter systems -vortex lines in liquid helium, flux tubes in type-II sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
1,339
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,239 publications
(1,356 citation statements)
references
References 314 publications
(439 reference statements)
15
1,339
0
2
Order By: Relevance
“…In a local minimum, jPj ¼ jNj from (6) and hSi is as given in (7). The ansatz functions for the scalar fields are a simple generalization of the Abrikosov-Nielsen-Olesen string [34,35] (see also [36])…”
Section: The String Ansatzmentioning
confidence: 99%
“…In a local minimum, jPj ¼ jNj from (6) and hSi is as given in (7). The ansatz functions for the scalar fields are a simple generalization of the Abrikosov-Nielsen-Olesen string [34,35] (see also [36])…”
Section: The String Ansatzmentioning
confidence: 99%
“…Apart from that, supersymmetric models with more complex vacuum manifolds and several types of kinks connecting the different vacua have also been discussed [13]. Special attention should be paid to configurations of strings or vortices [1, 14,15]. In particular, there are important results on quantum stabilization of strings [16][17][18] and strings/vortices/monopoles dynamics [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this modern guise, the cosmic string network may consist of both fundamental strings, D-strings and wrapped D-branes. Reviews of these recent stringy developments can be found in [5] and [10], while earlier work on cosmic strings from the 1980's and early 90's is summarized in [11,12].…”
Section: Introductionmentioning
confidence: 99%